EVALUASI KETERAMPILAN MENULIS YANG DIBUAT GURU SD DI KOTA MAGELANG - Mulyani, Mimin (Universitas Negeri Semarang, 2008)
In developing the language teaching evaluation system, communicative competence must be the most important thing to refer to. Thus, it is clear that the grading system used by elementary school teachers needs to be evaluated. The proses of datas analysis were focused on writing skill evaluation design which was appropriate to contextual approach and class based grading. The conclusion of this research was that the writing skill evaluation used by elementary student in Magelang was not the same, every group based on different teaching manual plan or Ã¢â¬ÅRPPÃ¢â¬Â, and different manual books. The way and the time for evaluation were also different. The type of questions for writing skill evaluation in Magelang elementary school were multiple choices, short question and essay. There are some evaluations and writing skill type questions which were appropriate with the basic evaluation on teaching manual plan and which were inappropriate with it. The character of contextual approach was not fix with the teaching manual plan given. The teaching evaluation system applied contextual approach, while the technique of grading applied the class based grading with the minimum quality. Kata Kunci: Evaluasi, Keterampilan Menulis, Guru SD